Dislodged Interatrial Septum Occluder was Found in an Incredible Place: A Case Report - Mehrdad Jafari Fesharaki; Azin Alizadehasl; Zahra Khajali; Melodi Farashi (International Journal of Cardiovascular Practice, 2019)
Secundum type atrial septal defect (ASD) is the most common type of interatrial septum defects. Transcatheter closure of secundum ASD has replaced traditional surgical ASD closure in most cases. Embolization of device is relatively uncommon (0.3%), but it can be a life-threatening situation that needs emergency open heart surgery. We presented a 44-year-old woman who underwent a successful ASD device closure, but the day after procedure, she presented with dyspnea and frequent paroxysmal supraventricular tachycardia with absence of device in interatrial septum (IAS) position. Further investigation by transesophageal revealed atrial septal occluder in the right pulmonary artery that extracted by surgery successfully.